Investigation of chemoresistance to first-line chemotherapy and its possible association with autophagy in high-risk neuroblastoma - Chen, Tingting; Zeng, Chenggong; Li, Zhuoran; Wang, Juan; Sun, Feifei; Huang, Junting; Lu, Suying; Zhu, Jia; Zhang, Yizhuo; Sun, Xiaofei; Zhen, Zijun (Frontiers in Oncology, 2022)
High-risk neuroblastoma (NB) is sensitive to chemotherapy but susceptible to chemoresistance. In this study, we aimed to analyze the incidence of chemoresistance in high-risk NB patients and to explore the role of autophagy in NB chemoresistance. We retrospectively analyzed the incidence of changing the chemotherapy regimen due to disease stabilization or disease progression during induction chemotherapy in high-risk NB patients, which was expressed as the chemoresistance rate. The autophagy levels were probed in tumor cells exposed to first-line chemotherapy agents. The sensitivity of tumor cells to chemotherapy agents and apoptosis rate were observed after inhibiting autophagy by transfection of shRNA or chloroquine (CQ). This study included 247 patients with high-risk NB. The chemoresistance rates of patients treated with cyclophosphamide + adriamycin + vincristine (CAV) alternating with etoposide + cisplatin (EP) (Group 1) and CAV alternating with etoposide + ifosfamide + cisplatin (VIP) (Group 2) was 61.5% and 39.9% (P = 0.0009), respectively. Group 2 had better survival rates than group 1. After exposure to cisplatin, cyclophosphamide, and etoposide, the autophagy-related proteins LC3-I, LC3-II, and Beclin-1 were upregulated, and the incidence of autophagy vesicle formation and the expression of P62 were increased. Chemotherapeutic agents combined with CQ significantly increased the chemotherapeutic sensitivity of tumor cells and increased the cell apoptosis. The downregulated expression of Beclin-1 increased the sensitivity of tumor cells to chemotherapeutics. Our results suggest that increasing the chemotherapy intensity can overcome resistance to NB. Inhibition of autophagy is beneficial to increase the sensitivity of NB to chemotherapy agents.